Seleksi Kacang Bambara (Vigna subterranea (L.) Verdcourt) Berumur Genjah Hasil Iradiasi Sinar Gamma Generasi M2 - Hafsah Ashri Noor Azizah; Noladhi Wicaksana; Dedi Ruswandi (Faculty of Agriculture, Pattimura University, 2017)
Mutation breeding using gamma-ray irradiation is one way to improve thevariability of bambara groundnuts. Improved variability can increase the effectiveness of selection on bambara groundnuts. The objective of this research was to obtain some genotypes of bambara groundnut of M2 generation that are of early maturity and high yield from gamma-ray irradiation through phenotypic selection. The experimental design was Spatial Plan, using the descriptive-comparative method. Bambara groundnuts accessions (KB-29 (1)) were treated with gamma-ray irradiation with different doses namely 100 Gy, 150 Gy, and 200 Gy. The results of this study showed that the phenotypic variability of the population irradiated by gamma rays 100 Gy, 150 Gy, and 200 Gy on the character of flowering time, harvest time, and all yielding ability characters was broad. The results of selection obtained 30 of the best genotypes that have advantages in the character of early maturity based on scoring value.